Being ordinary in extraordinary places: Reflective practice of the total situation in a total institution. - Riordan, DanielC. (Psychoanalytic Psychotherapy, 2008)
This paper examines a 'Foulkesian type' Balint group for psychiatry trainees set in a high secure forensic hospital. Within a Balint group, group processes and dynamics are not examined. Deviation from this format is construed as resistance, and destructively getting in the way of the primary task. This paper reports on a case-based reflective practice group operating on a more Foulkesian group analytic model and argues that the revised principles of method proposed here - paying attention to context; group processes; and creating an atmosphere where group curative factors are in play - can help trainees to sustain an emotional reservoir for their patients. Further, these principles do not get in the way of the primary task but can add to an understanding of the individual transference and counter-transference issues, and can place these in context within the organization and society. This is particularly important in total institutions such as forensic units. Clinical material from this group is used to support this claim.